Política e violência em Soledade – RS (1932-1938) - Filatow, Fabian (2015)
This paper is dedicated to study connections between politics and violence during the Vargas years in the state of Rio Grande do Sul. It has as reference the local disputes which occurred in the city of Soledade between 1932 and 1938. To that end, it is studied the consequences of the Combate do Fão, event that was inserted in the Constitutionalist Revolution; the local governments and the violence practices in the election periods, mainly; and the socialreligious movement of the Monges Barbudos which was repressed by the state as communists in the period of the consolidation of the Estado Novo. The reflection contributes to think the connection between violence and politics in the gaucha political history in the first phase of Vargas government, even though it was limited to Soledade. The analysis of contents is adopted as methodology during the research. Among the results obtained is pointed the political violence out in the Soledade region associated with the competition for regional and local power and important connections with the national political game. Firstly, the practice of violence aimed to suppress the opposition led by FUG against Flores da Cunha and Getúlio Vargas. In the second moment, the political violence began to fight against the florismo, mainly in 1935, which was present in that region as possible threat to both order and national security. It happened after authoritarian regime in 1937, when Monges Barbudos were inserted what legitimated an imposed repression.